2011
DOI: 10.1007/s12011-011-9105-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Manganese Deficiency and Added Cerium on Nitrogen Metabolism of Maize

Abstract: Manganese is one of the essential microelements for plant growth, and cerium is a beneficial element for plant growth. However, whether manganese deficiency affects nitrogen metabolism of plants and cerium improves the nitrogen metabolism of plants by exposure to manganese-deficient media are still unclear. The main aim of the study was to determine the effects of manganese deficiency in nitrogen metabolism and the roles of cerium in the improvement of manganese-deficient effects in maize seedlings. Maize seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Additionally, it was found that glutamate synthase (tr|A0A1D6NFL0|A0A1D6NFL0_MAIZE, tr|A0A1D6G281|A0A1D6G281_MAIZE) was also up-regulated in two varieties. Ammonia produced by reduction of NO 3 − or NO 2 − is toxic if it is accumulated in plant cells [37], and the up-regulation of glutamate synthase leads to an increase in the abundance of glutamate, which can be used for maize growth [38], and for eliminating ammonia produced under adverse conditions [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was found that glutamate synthase (tr|A0A1D6NFL0|A0A1D6NFL0_MAIZE, tr|A0A1D6G281|A0A1D6G281_MAIZE) was also up-regulated in two varieties. Ammonia produced by reduction of NO 3 − or NO 2 − is toxic if it is accumulated in plant cells [37], and the up-regulation of glutamate synthase leads to an increase in the abundance of glutamate, which can be used for maize growth [38], and for eliminating ammonia produced under adverse conditions [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Nitrate and Mn are essential nutrients in plants, and it has been reported that Mn deficiency decreases N uptake and metabolism ( Gong et al, 2011 ). Excessive NO 3 - was shown to enhance Cd uptake in Thlaspi caerulescens ( Xie et al, 2009 ) and wheat ( Li et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, Mn can influence NO 3 - reductase activity and is associated with photosynthesis in plants ( Botrill et al, 1970 ; Gong et al, 2011 ). Mn also influences N metabolism and regulates protein synthesis ( Jiang, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…These two enzymes are involved in glutamate synthesis, which is critical for decreasing ammonia levels. 25,26 Meanwhile, hydroxymethyltransferase, dihydrolipoyl dehydrogenase, and NAD-dependent malic enzyme were significantly up-regulated to synthesize serine, aspartate, and alanine, which also help to decrease ammonia levels (Figure 6C).…”
Section: Enriched Metabolic Pathways Of Drps In Salt-treated Jing724mentioning
confidence: 99%